Subjective Psychological Well-Being in Families with Blind Children: How Can We Improve It? - Sola-Carmona, Juan J.; Lopez-Liria, Remedios; Padilla-Gongora, David; Daza, María T.; Aguilar-Parra, Jose M. (Frontiers in Psychology, 2016)
The aim of this work was to examine family well-being in a sample of Spanish families with blind children. Sixty-one participants reported their perceived economic status, the level of job satisfaction, and state-anxiety symptoms. The participants of our study scored higher on state-anxiety and lower on material well-being than the normative sample, although these differences did not reach statistical significance. They also scored higher on job satisfaction and family satisfaction than the general population. A negative correlation was found between state-anxiety and material well-being (r = -.622, p = .001) and between state-anxiety and family satisfaction (r = -.578, p = .001). A positive correlation was found between material well-being and job satisfaction (r = .408, p = .001), and between material well-being and family satisfaction (r = .417, p = .001). Higher levels of material well-being, job satisfaction, and family satisfaction were associated with lower levels of anxiety in these families. However, no statistically significant correlation was found between family satisfaction and job satisfaction. Our results suggest that the family experience of having a disabled child is evolving, and this implies achieving greater job and family satisfaction than the normative samples, although anxiety scores continue to be higher and material well-being scores remain lower. On the whole, our results confirm that it is necessary to provide these families with more economic resources, which would have a positive impact on their subjective psychological well-being, decreasing their state-anxiety and increasing their satisfaction with life.